Improving teeth appearance from the impact of unhealthy lifestyle: a case report - Pribadi, Nirawati; Linawati; Rachmawati, Atika Nisaa; Ramadhan, Aqila Shabrina Dwi; Fadhillah, Revita Rizki (Universitas Airlangga, 2024)
Background: Tooth discoloration in one or more anterior teeth can cause significant aesthetic problem for patients because it affects the smile that relates to a person’s self-confidence. Thus, external bleaching is a viable treatment alternative. Discoloration stains on teeth are caused by smoking and the consumption of pigmented beverage such as coffee. Purpose: This case reports an external bleaching caused by an unhealthy lifestyle. Case: A 26- year-old female television presenter wanted to treat yellowish dark shade of her teeth and this made her feel less confident due to the yellowish dark shade teeth. Case Management: Teeth discoloration was managed with external bleaching using hydrogen peroxide 40%. After the treatment, the teeth shade increased from yellow-brownish to A2 with Vita Classic shade guide. Conclusion: The case report shows that external bleaching treatment produces brighter shade and increase self-confidence of the patient so she feels very satisfied.